ANALYSIS OF THE LEVEL OF SATISFACTION OF LISTENERS OF RADIO DEHASEN 88.5 FM (Descriptive Study of Dehasen University Students Bengkulu) - Vethy Octaviani; Rio Dinero (Universitas Dehasen Bengkulu, 2023)
Radio listeners are increasingly selective in choosing radio broadcast programs, so that the number of radio listeners is decreasing, plus the presence of other media causes a lack of listener interest in listening to radio. This is a problem for radio station managers such as Radio Dehasen 88.5 FM which is under the auspices of Dehasen University Bengkulu. The purpose of this study was to find out how much the level of listener satisfaction on Radio Dehasen 88.5 FM, especially among students at Dehasen University Bengkulu. This study uses the Uses and Gratification Theory which focuses on the use of media (uses) to get satisfaction (gratification). This research is a quantitative research with the method used is survey. The sample in this study amounted to 98 people. From the results of this study it can be seen that the intensity of listening to the radio by listeners of Dehasen 88.5 FM Radio is as much as 30.4% listening to the radio for 10-45 minutes, 53.6% listening for 46-90 minutes, 8.9% listening for 91-135 minutes, and 7.1% listened for 135-180. The Uses and Gratification theory shows that the main problem is not how the media changes audience attitudes and behavior, but how the media fulfills the personal and social needs of audiences. This study wants to know whether listening to the radio can fulfill listener satisfaction, namely information satisfaction, personal identity satisfaction, social interaction satisfaction, and entertainment satisfaction. These indicators are used to measure listener satisfaction in listening to the radio. Based on the average results of the research, the listener satisfaction level of Dehasen 88.5 FM Radio is in the Fairly Satisfied category with a percentage score of 49.324%. With these findings, it is hoped that it can provide input for the managers of Dehasen 88.5 FM Radio to further improve the quality of radio delivery that is tailored to listeners' interests and what things can satisfy these listeners so that Dehasen 88.5 FM Radio can continue to exist in the future and be able to compete with other radio stations.